73.3k views
1 vote
Explain how solve 4^(x+3)=7 using the change of base formula: (imaged below). Include the solution for x in your answer and round to the nearest thousandth

Explain how solve 4^(x+3)=7 using the change of base formula: (imaged below). Include-example-1
Explain how solve 4^(x+3)=7 using the change of base formula: (imaged below). Include-example-1
Explain how solve 4^(x+3)=7 using the change of base formula: (imaged below). Include-example-2
Explain how solve 4^(x+3)=7 using the change of base formula: (imaged below). Include-example-3
Explain how solve 4^(x+3)=7 using the change of base formula: (imaged below). Include-example-4
Explain how solve 4^(x+3)=7 using the change of base formula: (imaged below). Include-example-5

1 Answer

3 votes

we have the equation


4^((x+3))=7

Solve for x

Apply log of base 4 on both sides

so


\begin{gathered} \log_44^((x+3))=\log_47 \\ \\ (x+3)\operatorname{\log}_44=\operatorname{\log}_47 \\ \\ (x+3)=\log_47 \\ \\ x=\log_47-3 \\ \end{gathered}

Apply change of base

we have that


\log_47=(log7)/(log4)

substitute


\begin{gathered} x=(log7)/(log4)-3 \\ \\ x=-1.596 \end{gathered}

User Hannes Stoolmann
by
4.6k points